Monolith Passive Adsorbers Prepared with Hydrophobic Porous Silica Rods Coated with Hydrogel. (13th April 2018) - Zouari, Meriem; Bois, Laurence; Dugas, Vincent; Hbaieb, Souhaira; Chevalier, Yves; Kalfat, Rafik; Demesmay, Claire
ABSTRACT: This work focuses on the synthesis and characterization of porous silica monolith-based adsorbent materials. Materials with bimodal porosity (macro and meso) were prepared through a sol–gel process. The capacity of adsorption of organic molecules was ensured by grafting of hydrophobic organic coating on the silica surface. Alkylsilane chains or lauryl acrylate polymer were used for this purpose. The adsorption kinetic behavior of the produced materials was assessed through benzophenone adsorption studies in aqueous media. The results have shown that the macropore size of the monoliths had no effect on the adsorption capacity. The thicker organic layer prepared by polymerization of lauryl acrylate has decreased the adsorption kinetics without affecting the total adsorption capacity. The over-coating with additional external layer of hydrogel further slowed the diffusion of benzophenone thus better matches the passive-sampler requirements.